Mesrine. Public enemy #1 [videorecording (DVD)] - Richet, Jean-François; Sagnier, Ludivine, 1979-; Amalric, Mathieu, 1965-; Cassel, Vincent, 1966- (Mesrine saga, 2011)
In the climactic second part of the Mesrine saga, Jacques Mesrine is back in France after his brazen assault on the maximum-security prison from which he daringly escaped. Once again in police custody and facing stern justice for his crime, 'the man of a thousand faces' escapes directly from the courtroom after kidnapping the judge at gunpoint. The life of Jacques comes once and for all to a full bloody circle.